Revolutionizing the management of enlarged prostate: unveiling the success of robot-assisted simple prostatectomy using Versius robotic system - Harris Hassan Qureshi; Mahar, Naveed Ahmed; Rehan Mohsin; Riaz Ahmed Leghar; Muhammad Fayyaz; Usman Qamar (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the outcomes of robot-assisted simple prostatectomy by analysing postoperative complications and patient-reported outcomes, and to scrutinise the effectiveness and safety of a surgical robotic system. Method: The prospective cohort study was conducted at the Department of Robotics and Minimally Invasive Urology, Sindh Institute of Urology and Transplantation, Karachi, from November 2021 to June 2023, and comprised patients with treatment-resistant lower urinary tract symptoms) attributed to significant prostatic enlargement exceeding 80ml on transrectal ultrasound, and who were slated for robot-assisted simple prostatectomy. Perioperative and postoperative data was noted along with outcomes and complications. Data was analysed using SPSS 25. Results: There were 82 male patients with mean age 66.6±8.88 years, mean duration of lower urinary symptoms 4.59±1.59 years, and mean volume of prostate 133.24±27.31ml. The mean procedure time was 160.56±33.04 minutes, and mean blood loss was 678.05±314.85ml. Baseline maximum flow rate on uroflowmetry was 5.86±1.59ml/s compared to 17.00±7.57ml/s postoperatively (p=0.0001). Conclusion: The robot-assisted simple prostatectomy was found to be a safe procedure with acceptable patient outcomes. Key Words: Benign prostatic enlargement, Robot-assisted simple prostatectomy, Lower urinary tract symptoms, Versius robotic system.